Penentuan Pembelian Bahan Baku Dan Jumlah Produksi Makanan Menggunakan Fuzzy Mamdani Pada Usaha Kedai Martabak XYZ - Sutrisno, Ade; Fajrin, Fajrin; Anwar, Saiful; Azizi, Sandi; Setyawan, Agus (Journal of Machine Learning and Soft Computing, 2019)
Various problems that often arise in this world often invite uncertainty, fuzzy logic is one method for analyzing systems that contain uncertainties, especially in the business world. In this study analyzing the problem of martabak cake sellers in the production process using the mamdani method or often also known as the min-max method. The problem faced is determining the raw material requirements and the amount of cake that must be produced. The results of the study show that for the raw materials available in such a way that at week 6 the seller needs to produce 720 servings of martabak cake.